Pre-diagnostic “chronic life stressors” and their association with breast cancer outcomes: A cross-sectional observation study - Biju Azariah M; Arumugam Velappan (Asian Journal of Medical Sciences, 2024)
Background: Breast cancer is widely studied for its psychosomatic aspects owing to its high prevalence among women and the impact of chronic life stressors on its development and outcomes. Aims and Objectives: This study aimed to evaluate the association between previous chronic stressors and breast cancer diagnosis, duration of presentation to a health-care facility stage at presentation, tumor profile, treatment compliance, treatment-induced complications, and outcomes. Materials and Methods: This cross-sectional observational study included 200 breast cancer patients. Patients were interviewed post-treatment to collect data on marital status, socioeconomic status, occupation, education, and emotional events, using the Holmes and Rahe stress scale. Scores were categorized as low-, medium-, or high-risk for disease development. Results: Low-level chronic stress was the most prevalent in patients with stage I disease (93%), followed by stage II (87%), stage III (72%), and stage IV (52%). Moderate-level chronic stress increased with the disease stage, being the lowest in stage I (7%) and the highest in stage IV (48%), and this was significant (P=0.01). The median duration from symptom recognition to presentation was <4 weeks in 81–62% of patients with low and moderate stress, respectively. For those with moderate chronic stress, 62% presented within 4 weeks and 38% took >4 weeks, with a significant P=0.01. Conclusion: Recognizing and addressing pre-diagnostic chronic stress is crucial for breast cancer management because it influences the cancer stage at diagnosis and the time of health-care presentation. Integrating psychosocial support into cancer care can improve treatment effectiveness and patient well-being.